Increased postural stiffness during challenging postural tasks in patients with knee osteoarthritis with high pain sensitization. (January 2019) - Hirata, R.P.; Skou, S.T.; Simonsen, O.; Rasmussen, S.; Laursen, M.; Graven-Nielsen, T.
Abstract: Background: Postural stability is affected in knee osteoarthritis patients who present with pain but the link to pain sensitization is unclear. Methods: Patients with knee osteoarthritis completed the Knee Injury and Osteoarthritis Outcome Score and pressure pain thresholds were assessed bilaterally at the knee, lower leg and forearm prior to standing quietly (1 min) on a force platform in four conditions: Firm surface with open eyes, firm surface with closed eyes, soft surface with open eyes, and soft surface with closed eyes. Pain intensity during standing was assessed via numerical rating scale. Postural stability was assessed by the range, velocity, and standard deviation of the Center of Pressure (CoP) extracted from the force platform. The means of three repeated measures per standing condition were analysed. High-sensitization and low-sensitization groups were defined based on bilateral pressure pain thresholds from leg and arm. Findings: Fifty-six patients were included. Compared with the low-sensitization group, the high-sensitization group demonstrated 1) smaller pressure pain thresholds at the knee ( P  < 0.05) although the Knee Injury and Osteoarthritis Outcome Score and pain intensity were not significantly different between groups, and 2) smaller range of the CoP in the anterior-posterior direction during the soft surface with closed eyes condition ( P  < 0.05). Interpretation: Smaller CoP range suggest that patients with more widespread pain sensitivity have increased postural stiffness compared with the low-sensitization group. The greater stiffness found in high-sensitization patients under sensory restrictions (closed eyes and reduced proprioception) might relate to restricted integration of sensory information due to widespread pain sensitization. Highlights: Larger anterior-posterior postural sway compared with medial-lateral direction Larger widespread pain sensitization relates to higher knee pain sensitivity. Larger widespread pain sensitization relates to increased postural stiffness.